Trade Preferences from a Policy Perspective - Maria Persson (Lund University, School of Economics and Management, Department of Economics, 2013)
The aim of this paper is to offer a comprehensive overview of non-reciprocal trade preferences. Legal and economic aspects are discussed, and in particular, focus is put on how the specific design of preference programs influence whether or not preferences will have their intended effects. The paper starts by summarizing the historical and legal background of non-reciprocal trade preferences, and thereafter discusses how preferences are intended to work from an economic point of view. Further, the paper discusses ways to determine whether or not preferences meet their intended targets, and outlines in some detail how preference programs differ in their design. The question of how trade preferences could have negative effects for recipient and non-recipient countries is explored, and the paper concludes by discussing whether trade preferences will be a useful policy alternative in the future.
Keywords: F13; F15; 330; Unilateral trade preferences; non-reciprocal trade agreements; GSP